(untitled) (Nordic Journal of Practical Theology, 2022)
This article asks how activities such as confirmation work, leadership training and youth group, create transitions between communities for youth in the local church. Utilizing an action research design, the material is established in cooperation with practitioners from four different youth ministries. The methods used are field work observation and interviews. Drawing on the theoretical framework of symbolic boundaries, boundary object, boundary crossings and boundary practices that make transformation happen, the article has analyzed material from a case congregation’s youth activities. The analysis identifies several boundary objects that enable the adolescents to participate in the different activities. Additionally, the voluntary youth leaders became bridge builders for the confirmands into leadership training and youth camp and group. Finally, the article asks if the different boundary objects and crossings transform or create new practices.